Pemberdayaan Madin Al Hikmah untuk Meningkatkan Kualitas Pembelajaran Al-Qur’an Anak di Jegles Tarokan Kediri - Mega Dwi Rahayu (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
One of the informal forums in the religious or religious field that is dominant in the community is Madrasah Diniyah or commonly referred to as TPQ. Although there have been many Madin who have been successful with the number of students or students and good administration, but there are also many Madin who experience ups and downs, especially since this Madin is still counted as a religious education institution that was only built for about a year and a half. This Madin is located in an inner rural environment so that the number of students in this Madin is still minimal. Empowerment carried out by researchers at Madin al-hikmah is to participate in learning activities at Madin al-hikmah, provide assistance to santri children in Madin al-hikmah as well as approach the madin caregivers and children in the Jegles hamlet area. In addition to approaching the community and children, the researchers also carried out empowerment in the environment and classes at Madin Al hikmah because the condition of Madin Al Hikmah was just built so that infrastructure and places for learning were still minimal. By empowering at Madin al hikmah, it is hoped that it can help children improve the quality of learning the Qur’an and can add insight and experience for researchers.